2022
DOI: 10.1002/marc.202200208
|View full text |Cite
|
Sign up to set email alerts
|

Progress, Challenge, and Perspective of Fabricating Cellulose

Abstract: Cellulose as the most abundant biopolymers on Earth, presents appealing performance in mechanical properties, thermal management, and versatile functionalization. Developing fabrication methods to design functional materials and open new application areas. However, cellulose is hard to be dissolved or melt due to its recalcitrant property. Herein, the recent progress of fabricating cellulose is summarized. First, the unique hierarchical structure of cellulose is fully investigated and the resulted processabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 211 publications
(302 reference statements)
0
1
0
Order By: Relevance
“…Considering the advances over the past twenty years, several challenges have been identified that hinder the transition of nanocellulose production and utilization to a large industrial scale. To overcome the difficulties, improvements in the production efficiency with environmentally friendly approaches and less energy-consuming processes to lower the cost are strongly recommended [ 146 , 147 , 148 , 149 , 150 , 156 , 157 ]. In this regard, quite recently, some researchers in the field have highlighted the importance of revisiting the fundamental understanding of nanocellulose–water interactions and the colloidal behavior of nanocelluloses in solving some of the challenges encountered [ 146 , 147 ].…”
Section: Emerging Applications and Future Developmentmentioning
confidence: 99%
“…Considering the advances over the past twenty years, several challenges have been identified that hinder the transition of nanocellulose production and utilization to a large industrial scale. To overcome the difficulties, improvements in the production efficiency with environmentally friendly approaches and less energy-consuming processes to lower the cost are strongly recommended [ 146 , 147 , 148 , 149 , 150 , 156 , 157 ]. In this regard, quite recently, some researchers in the field have highlighted the importance of revisiting the fundamental understanding of nanocellulose–water interactions and the colloidal behavior of nanocelluloses in solving some of the challenges encountered [ 146 , 147 ].…”
Section: Emerging Applications and Future Developmentmentioning
confidence: 99%